Zinc pot shaft sleeve bearing, preparation method and application thereof
By using a combined design of heat-resistant alloy substrate, alloy transition layer, ceramic coating and fiber cloth on the zinc pot bearing shell, the existing zinc pot bearing shell has solved the problem of short and fragile life, achieving longer service life and more stable operation.
Patent Information
- Application Number
- CN202411896681.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing zinc pot bearing bushings have problems with short life and fragile tiles, especially under multiple effects such as high temperature-corrosion-wear-stress, which leads to its short service life and easy to damage.
A zinc pot bearing bushing is used, and its base material is a heat-resistant and corrosion-resistant alloy. The counter-milling parts of the bearing bushing and bearing bushing are covered with an alloy transition layer and a ceramic coating, and a fiber cloth is provided on the ceramic coating. The fiber cloth is fixed to the bearing bushing, and the remaining parts are coated with silicon-based resin.
By introducing ceramic-ceramic friction pairs and fiber cloth, the service life of the bearing bushing is significantly extended, the wear between the ceramics is reduced, and the pot residue is effectively captured, avoiding local excessive wear of the friction pair.
Smart Images

Figure CN119351922B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of surface technology, and in particular to a zinc pot shaft sleeve bearing shell, a preparation method and application thereof. Background Art
[0002] Hot-dip galvanizing is one of the conventional and most effective means to improve the environmental corrosion resistance of steel strips. The zinc pot is the main place for hot-dip galvanizing of steel strips. Since the sleeves and bearings in the zinc pot are immersed in molten zinc (or zinc alloy) at high temperature for a long time, and the sleeves and bearings need to rotate relatively smoothly during the galvanizing process to ensure the continuity and stability of the strip, the tension generated by the steel strip on the pot roller during operation will be transmitted to the sleeves and bearings, so that the sleeves and bearings are under the multiple effects of high temperature, corrosion, wear and stress for a long time, and are the most easily worn parts in the zinc pot.
[0003] In order to extend the service life and operational stability of bushings and bearings, domestic and foreign countries have conducted continuous exploration and practice on bushing and bearing strengthening technology for more than 100 years, and have developed a variety of wear-resistant and corrosion-resistant bushings and bearings. The bushings and bearings that are currently in use can be divided into two categories from the perspective of the material system. One is alloy bushings-alloy bearings. Typical manufacturers using this type of bearing include Sinosteel Hantai, Jiulian, and Wall, etc. Its main features are simple production, low price, and relatively stable operation. The main problems are rapid wear and generally short service life. The other is alloy bushings-ceramic bearings. There are many representative manufacturers, including Fangdeng, Duma, WearGaurd, Hitachi, Kyocera, TOCALO and other leading foreign manufacturers. This type of bushing and bearing has the main advantage of a longer service life, but the stability is relatively poor. If the ceramic tile is even slightly damaged, problems such as tile breakage may easily occur. This is because ceramic tiles are actually ceramic tiles that are simply physically matched with alloy tile seats in an inlaid form, and the CTE of ceramics and alloys are usually quite different. During service in the zinc pot, zinc liquid and pot slag may fill into the assembly gap, and the tension and extrusion during service may cause local stress concentration and breakage. In addition, for the same reasons mentioned above, there is a greater risk of ceramic tiles breaking due to thermal expansion and contraction when cooling, so manufacturers usually only promise a single continuous service life (or clearly stipulate that the bearing shells cannot be taken out of the crucible and reused repeatedly).
[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of short life and fragile bearings in the prior art, and to provide a zinc pot shaft sleeve bearing, a preparation method and an application thereof.
[0006] In order to achieve the above-mentioned purpose, the present invention discloses a zinc pot shaft sleeve and bearing, characterized in that the base material of the shaft sleeve and bearing is a heat-resistant and corrosion-resistant alloy, the grinding part on the base material of the shaft sleeve is covered with an alloy transition layer and a ceramic coating, the grinding part of the bearing is provided with an alloy transition layer, a ceramic coating, and a fiber cloth in sequence from the inside to the outside, the fiber cloth is fixed on the bearing, and the remaining parts of the shaft sleeve and bearing except the grinding part are coated with a silicone-based resin.
[0007] The substrate is a cobalt-based heat-resistant alloy or 316L stainless steel.
[0008] The ceramic coating on the shaft sleeve and the bearing shell is aluminum oxide, zirconium oxide, silicon nitride or zirconium silicate, and the thickness of the ceramic coating is 300-500 μm.
[0009] The fiber cloth is made of silicon nitride or silicon carbide, and the number of layers of the fiber cloth is 3 to 5.
[0010] The alloy transition layer is any one of NiCr, NiCrAlY, CoCrAlY and modified alloys thereof, and the thickness of the alloy transition layer is 100-500 μm.
[0011] The present invention also discloses a method for preparing the zinc pot shaft sleeve and bearing, which comprises the following steps:
[0012] S1, design the sleeve and bearing drawings according to the production requirements of the hot-dip galvanizing line;
[0013] S2, process the bearing bushing blank according to the drawing;
[0014] S3, depositing alloy coating on the wear part of the sleeve and bearing;
[0015] S4, continuing to deposit a ceramic coating on the alloy coating;
[0016] S5, finish machining the sleeve and bearing according to the drawing;
[0017] S6, the remaining parts are coated with silicone-based resin;
[0018] S7, fiber cloth is arranged on the shaft sleeve and bearing shell.
[0019] In step S4, a sealing process is performed after the coating is deposited.
[0020] The invention also discloses the application of the zinc pot shaft sleeve and bearing bush in a hot-dip galvanizing or zinc alloy production line.
[0021] The invention also discloses the application of the zinc pot shaft sleeve and bearing shell in a hot dip aluminum silicon production line.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] 1. Since the bushings and bearings are immersed in zinc (or zinc alloy) liquid for a long time, the base material of the bushings and bearings should be selected from heat-resistant and corrosion-resistant alloys; and in order to ensure that the sunken roller can rotate stably, there needs to be relative sliding between the bushing and the bearing, and there will be a certain tension when the steel belt moves, so that the contact parts of the bushing and the bearing need to bear additional wear and stress. If these parts are not effectively strengthened, the bushing / bearing will soon fail as a whole due to abrasion. Therefore, the selection of the bushing and bearing friction pair is crucial. At present, the bushing and bearing friction pairs selected by domestic and foreign manufacturers are not the same, but the purpose is to reduce the degree of wear and corrosion of the bushing and bearing, thereby extending the service life of the bushing and bearing. The present invention is different from the previous alloy-alloy and alloy-ceramic friction pairs. It adopts ceramic-ceramic friction pairs. This is because ceramics have relatively stable chemical properties and do not react with the alloy liquid in the zinc pot. At the same time, ceramics have high hardness and wear resistance, which can greatly extend the service life of the bushing and bearing.
[0024] 2. Although ceramics have good wear resistance and corrosion resistance, the reason why manufacturers do not use ceramics against ceramics is that when materials with similar hardness wear, they will produce higher contact pressure and friction on their contact surfaces. Although ceramics are hard, they are brittle. Long-term friction will cause tiny particles on their surface to fall off, thereby aggravating wear. Therefore, the present invention introduces several layers of fiber cloth between the ceramic-ceramic friction pair to separate the two hard ceramic surfaces. At the same time, since the fiber cloth has a certain flexibility, the contact stress of the friction pair becomes more dispersed, thereby reducing the wear between the ceramics. In fact, the friction pair in the zinc pot sometimes faces another problem: the embedding of pot slag between the friction pairs (the pot slag is a hard compound formed by the chemical reaction between the zinc alloy liquid and the steel strip, oxygen and other impurities). After the small-sized pot slag flows with the alloy liquid to the friction pair and adheres, it will cause local excessive wear of the friction pair, and then embed in the soft side, aggravating the wear between the friction pairs (the mechanism of action is similar to the aforementioned ceramic-ceramic wear). The fiber cloth introduced in the present invention is woven from fiber bundles. There must be certain gaps between the fiber bundles and between the weaving patterns. At the same time, there are inevitably more gaps between the multiple layers of cloth. If there is slag moving to the friction pair position with the alloy liquid, the fiber cloth can capture the slag in the above-mentioned gap in time, thereby reducing the impact of the slag on the friction pair.
[0025] 3. Currently, ceramic bearings on the market are usually assembled with pure ceramic bearings and metal bearing seats at high temperature. During the assembly process, they are prone to premature failure due to "broken bearings" due to improper control of assembly clearance and processing accuracy. The present invention directly uses spraying / laser technology to deposit the above-mentioned composite coating on the sleeve and bearing, avoiding the above-mentioned problems and ensuring the consistency of the life of the sleeve and bearing. According to the material of the covering coating and the requirements for the coating performance, appropriate processes need to be used for preparation on the sleeve and bearing. In particular, in order to improve the matching of the coefficient of thermal expansion (CTE) of the ceramic coating and the substrate, it is usually necessary to deposit an alloy transition layer before depositing the ceramic layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the typical structure of the sleeve-bearing friction pair;
[0027] Figure 2 This is the metallographic structure morphology of the cross section of the sample in Example 1.
[0028] The numbers in the figure represent:
[0029] 1-sleeve; 2-bearing shell; 3-alloy transition layer; 4-ceramic layer; 5-fiber cloth. DETAILED DESCRIPTION
[0030] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0031] Example 1
[0032] (1) Design the sleeve and bearing drawings according to the production requirements of the hot-dip galvanizing line;
[0033] (2) Process the bearing sleeve blank according to the drawing;
[0034] (3) A NiCr alloy coating with a thickness of 0.15 mm was sprayed on the sleeve and the bearing using atmospheric plasma spraying technology. The atmospheric plasma spraying process parameters are shown in Table 1;
[0035] (4) Use atmospheric plasma spraying technology to spray 0.35mm thick Al on the sleeve and bearing. 2 O 3 Ceramic coating, and the coating parts are sealed with silicon-based resin. The atmospheric plasma spraying process parameters are shown in Table 1. The microscopic cross-sectional morphology of the coating on the surface of the furnace sample after spraying is shown in Figure 2 As shown;
[0036] (5) After finishing the sleeve and bearing according to the drawing, the non-spraying parts are coated with silicone-based resin;
[0037] (6) Install 3 layers of Si on the bearing shell 3 N4 Fiber cloth.
[0038] Table 1 Atmospheric plasma spraying process parameters
[0039]
[0040] Comparative Example 1
[0041] Cobalt-based alloy sleeves and cobalt-based alloy tiles from a certain manufacturer are used.
[0042] Comparative Example 2
[0043] Adopt a cobalt-based alloy sleeve and Al 2 O 3 Ceramic tiles.
[0044] Comparative Example 3
[0045] Only one layer of Si is installed on the bearing shell 3 N 4 Fiber cloth, the rest is the same as in Example 1.
[0046] Comparative Example 4
[0047] 7 layers of Si are installed on the bearing 3 N 4 Fiber cloth, the rest is the same as in Example 1.
[0048] Comparison between Example 1 and Comparative Example 1 and Comparative Example 2:
[0049] The sinking rollers of a hot-dip galvanizing (ZMA) production line of a domestic steel plant were produced using the bearings and bushings of Comparative Example 1, Comparative Example 2, and Example 1. After 15 days of continuous use, the sinking roller of Comparative Example 1 began to shake. After stopping the machine to remove the bearing sleeves and bushings, the bearing sleeves and bushings were cleaned and inspected, and it was found that the bearing sleeves and bushings were severely worn, and the wear amount (maximum wear size on one side, the same below) exceeded 1.0mm; after 40 days of continuous use, Comparative Example 2 was stopped for inspection as usual. After stopping the machine to remove the bearing sleeves and bushings, the bearing sleeves and bushings were cleaned and inspected, and the wear amount of the bushings was very small (because the zinc alloy on the friction pair of the bearing sleeves and bushes cannot be completely removed after immersion in the zinc pot and then de-zincification, so the actual inspection The measurement error is large (ranging from 0.1 to 0.2 mm). Since the detected wear is less than the actual detection error, it is not marked, the same below). The sleeve wear reaches about 1.0 mm. After 40 days of continuous use in Example 1, it is normally shut down for inspection. After the sleeve and bearing are taken out after shutdown, the sleeve and bearing are cleaned and inspected. The sleeve and bearing wear is still very small. After continuing to be used online for 40 days, the fiber cloth of the bearing shows a small amount of wear, and a small amount of slag is attached to the fiber cloth. It can be continued to be used after replacing the new fiber cloth. It can be seen that the service life of the sleeve and bearing in Example 1 is significantly extended compared with Comparative Examples 1 and 2, and there is no need to replace the sleeve and bearing after use. Only the fiber cloth needs to be replaced to continue to use it. Therefore, the actual use effect of Example 1 is also significantly better than the current conventional sleeve and bearing.
[0050] Comparison between Example 1 and Comparative Example 3 and Comparative Example 4:
[0051] The comparison point between Example 1 and Comparative Examples 3 and 4 is the difference in the number of fiber cloth layers. The inventor has verified it in an experimental pot (high aluminum ZMA), and the comparison is as follows: After 30 days of continuous use of Example 1, the experiment ended normally, and no abnormal shaking of the experimental roller was found during the experiment; after about 21 days of continuous use of Comparative Example 3, the experimental roller began to shake slightly, and continued to run for about 24 days. The experimental roller shook more violently. After stopping for inspection, it was found that the fiber cloth in the center of the contact with the sleeve was completely worn out, and the corresponding part of the sleeve was severely worn. This is because the wear resistance of a single-layer fiber cloth is limited, and the effect of capturing pot slag and improving wear is limited; the experimental roller of Comparative Example 4 cannot run smoothly for a long time after installation. This is because the fiber is soft. After too many layers, it is easy to cause stacking deformation inside the fiber due to uneven force during the rotation process, thereby causing irregular changes in the supporting force of the experimental roller, resulting in the experimental roller being unable to run normally and smoothly. In addition, too many layers of fiber cloth will also increase the difficulty of installation and increase the manufacturing cost. Therefore, the 3 to 5 layers specified in the present invention are the preferred number of layers.
[0052] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A zinc pot sleeve bearing, characterized in that: The base materials of the shaft sleeve and bearing are all heat-resistant and corrosion-resistant alloys, the wear-resistant parts of the shaft sleeve and bearing base materials are covered with ceramic coatings, and the remaining parts are coated with silicone-based resins; the ceramic coating on the bearing side is covered with multiple layers of fiber cloth, and the fiber cloth is fixed on the bearing. Before depositing the ceramic layer, an alloy transition layer needs to be deposited, and the alloy transition layer and the ceramic layer are sequentially deposited on the shaft sleeve and the bearing by supersonic flame spraying, plasma spraying or laser cladding technology; The ceramic coating on the sleeve and the bearing shell is aluminum oxide, zirconium oxide, silicon nitride or zirconium silicate, and the thickness of the ceramic coating is 300-500 μm; The fiber cloth is made of silicon nitride or silicon carbide, and the number of layers of the fiber cloth is 3 to 5.
2. A zinc pot sleeve bearing as claimed in claim 1, characterized in that: The substrate is a cobalt-based heat-resistant alloy or 316L stainless steel.
3. A zinc pot sleeve bearing as claimed in claim 1, characterized in that: The alloy transition layer is any one of NiCr, NiCrAlY, CoCrAlY and modified alloys thereof, and the thickness of the alloy transition layer is 100-500 μm.
4. A method for preparing a zinc pot sleeve bearing according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, design the sleeve and bearing drawings according to the production requirements of the hot-dip galvanizing line; S2, process the bearing bushing blank according to the drawing; S3, depositing alloy coating on the wear part of the sleeve and bearing; S4, continuing to deposit a ceramic coating on the alloy coating; S5, finish machining the sleeve and bearing according to the drawing; S6, the remaining parts are coated with silicone-based resin; S7, fiber cloth is arranged on the shaft sleeve and bearing shell.
5. A method for preparing a zinc pot sleeve and bearing as claimed in claim 4, characterized in that: In step S4, a sealing process is performed after the coating is deposited.
6. Use of the zinc pot sleeve and bearing as claimed in any one of claims 1 to 3 in a hot-dip galvanizing or zinc alloy production line.
7. Application of the zinc pot sleeve and bearing as claimed in any one of claims 1 to 3 in a hot dip aluminum silicon production line.
Citation Information
Patent Citations
Molten aluminum corrosion resisting roller
CN110218996A
Elastic heading tape arrangement for labeler
CN2586656Y
Roller dipping device for hot dip galvanizing bath
CN2811322Y